Keefektifan Metode Role Play untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran Budi Pekerti Berbahasa Mandarin - Lusiani Giarto; Budi Hermawan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Characteristics learning has the goal of imparting ethical or morals. According to the Ethics Learning theme "Chapter 12 Giving advice and Chapter 13 Caring for friends" which were covered during the research, the researcher t chose the title "The Effectiveness of the Role Play Method for Increasing Students' Understanding of the Chinese Language Ethics Subject." Data measurement uses quantitative methods. Character Building learning utilizes the Chinese language role play method to help students understand the learning theme while training them to speak Chinese confidently in front of the class. The data collected for measurement consists of quiz results completed by students. The quiz results reveal that many students have not met the competency limits. In other words, role play method in this research has not yet achieved the targeted success. The main factor that influences the success or failure of research on the role play method is insufficient practice time, preventing students to understanding and speaking fluently in Chinese during role play dialogues. What students are currently doing is still at the reading stage, their body movements do not align with the practice required by the theme.